Theoretical Approaches on Optimal Capital Structure - MARIA ZENOVIA GRIGORE; MARIANA GURĂU (Global Economic Observer)
F. Modigliani and M. Miller demonstrated in 1958 that in the context of perfect market the financial structure of the firm does not influence its value. Since then, many researchers have approached the issue of financial structure in less restrictive hypotheses. Without reaching a consensus, they have tried to prove that the optimal capital structure exists. The goal of this article is to synthesize the literature on the financial structure and to relate the theories to known empirical evidence. The main models of the optimal financial structure belong to the agency theory, the signalling theory, the transaction cost economics and the pecking order theory. Financing decision varies according to a number of factors that may influence capital structure differently: firm profitability, dividend policy, growth opportunities, asset specificity, corporate tax shield, company size and some macroeconomic factors such as inflation rate and capital market condition.